Can leisure education effect on screen time and perceived leisure benefits for college students? - Özkara, Abdullah Bora; Mulazimoglu, Olcay; Somoglu, Mustafa Baris; Kirkbir, Fatih; Tokul, Erdi; Aydemir, Burakhan; Senturk, Halil Evren; Dalbudak, Ibrahim; Ozcilingir, Ozgun Mirac (Frontiers in Psychology, 2024)
Background: Since children and adolescents usually spend their theoretical course time at schools, they experience many negative effects of inactivity and physical inactivity. They are disadvantaged in terms of facing many health and social problems due to lack of physical activity. This sedentary life increases their exposure to screens and the time they spend sitting. Aim of the study: The first aim of this research is to conduct an experimental study to reduce the excessive screen time of college students with an exercise intervention. The second aim of the study is to examine the perceived benefits of leisure activities of students with an exercise intervention. Methods: In this direction, the study group of the research, which was conducted as an experimental study, consisted of 176 [74 female (42.0%), 102 male (58.0%)] students studying in the department of mathematics at college. In the study, the screen exposure time of students was measured with the "Screen time scale for youth and adolescents" along with a personal information form. In addition, the "Perceived Leisure Benefit Scale" scale was used to evaluate the participants' awareness of the benefits obtained from leisure activities. Results and conclusion: According to the findings of the research, it was determined that there was a positive and significant decrease in the screen time of the experimental group participants of students who participated in the research before and after the exercise intervention. In the Leisure Benefit Scale, it was observed that there were significant positive differences in favor of the experimental group.